Transforming rural China : how local institutions shape property rights in China - Chen, Chih-Jou Jay, 1966- (RoutledgeCurzon studies on China in transition, 2004)
It is often assumed that privatization leads to profit, and that well-delineated property rights and a strong private sector will help boost economy. This book investigates the property rights in Chinese enterprises in the reform era.